Diversity of aphids and their parasitoids and predators in alfalfa crop - Mendes, Simone; Cervino, Marcia Nascimento; Bueno, Vanda Helena Paes; Auad, Alexander Machado (Pesquisa Agropecuaria Brasileira, 2000)
This work was carried out with the objective of showing the diversity of aphids and their predators and parasitoids, as well as the influence of the climatic factors on these insects in alfalfa crop. The survey was done weekly from April/95 to March/96. Four species of the aphids were found: Therioaphis trifolii (Monel) f. maculata, Acyrthosiphon pisum (Harris), A. kondoi Shinji and Aphis craccivora Kock, which were present in the crop during all the survey period, with the population peaks in November/95, July/95, December and April/96, respectively. Predator insects belong to families: Coccinellidae, Syrphidae, Anthocoridae, Geocoridae and Chrysopidae were found. Species of Coccinellidae occurred during all the survey period, with the population peak in the end of December with 20 mm of rainfall and 22.6oC. The Syrphidae species reaching higher numbers in April/95, with 53 mm of rainfall and 21oC. Orius sp. was the only specie of Anthocoridae, with a peak in the end of December/95, under the same conditions as to Coccinellidae. Two species of the parasitoids were found: Aphidius colemani Viereck and A. ervi Haliday with the populacional peak in June/95 at 16oC.